The Effects of Spiritual Wellbeing on Self-Perceived Health Changes Among Members of the Church of England During the COVID-19 Pandemic in England - Village, Andrew (Journal of religion and health, 2023)
This paper tests whether changes in spiritual wellbeing were correlated with self-rated changes in mental and physical health after controlling for changes in psychological wellbeing in a sample from the Church of England taken during the third national COVID-19 lockdown in 2021. During the third lockdown in England an online survey, named Covid-19 and Church-21, was delivered through the Qualtrics XM platform from 22 January to 23 July 2021. The responses included 1878 Anglicans living in England. The change in spiritual wellbeing scale was produced using self-reported changes in the frequency of key spiritual practices (prayer and Bible reading), trust in God, the quality of spiritual life, and spiritual health. Changes in mental and physical health were assessed using single self-report items. Changes in psychological wellbeing were assessed using the Index of Balanced Affect Change (TIBACh). After controlling for changes in psychological wellbeing, better change in spiritual wellbeing was positively correlated with better change in both mental and physical health. Negative affect may have mediated the relationship between spiritual wellbeing and both mental and physical health, and positive affect may also have mediated the relationship with mental health. The results suggest changes in spiritual wellbeing, as defined within a Christian religious context, may have had positive effects in promoting better mental and physical health during a sudden crisis such as the COVID-19 pandemic.